Timing of auxin treatment affects grape berry growth, ripening timing and the synchronicity of sugar accumulation. (21st October 2021) - Davies, C.; Böttcher, C.; Nicholson, E.L.; Burbidge, C.A.; Boss, P.K.
Abstract: Background and Aims: Climate change has resulted in earlier berry development and compressed harvests creating problems with harvesting and winery logistics and causing undesired modifications to grape and wine composition, such as elevated concentration of berry sugar and wine alcohol. Auxin treatment of grapevine bunches prior to veraison can counteract these adverse changes by delaying berry maturation. The most efficacious timing of 1‐naphthaleneacetic acid (NAA) application along with the effects of application timing on berry growth, and berry and wine composition are yet to be identified. Methods and Results: Cabernet Sauvignon bunches were treated with 50 mg/L NAA at three different times prior to, and at, veraison. The nearer to veraison the NAA application the longer the delay in harvest. Compared with the Control the NAA treatment reduced berry shrivel and increased the synchronicity of berry populations in terms of the accumulation of TSS with only minor effects on berry composition and wine volatile compounds. Conclusions: Auxin treatment delayed ripening, reduced berry shrivel and increased ripening synchronicity with little effect on berry and wine composition. Significance of the Study: Auxin treatment of grape bunches could be used to manage problems caused by climate change, including, compressed harvests and ripening under hotter conditions, in a targeted manner in existing vineyards.